2016
DOI: 10.1097/mpg.0000000000001075
|View full text |Cite
|
Sign up to set email alerts
|

Infant Colic—What works

Abstract: Probiotics, in particular L reuteri, and preparations containing fennel oil appear effective for reducing colic, although there are limitations to these findings. The evidence for maternal dietary manipulation, lactase, sucrose, glucose, and simethicone is weak. Further well-designed clinical trials are required to strengthen the evidence for all of these interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 63 publications
0
37
0
1
Order By: Relevance
“…Thus, our analysis more precisely defines the role of probiotics for treating infantile colic. A more recent systematic review by Harb et al [17] focused on interventions in breast-fed infants only and concluded that probiotics, in particular L. reuteri , appear effective for reducing colic, although there are limitations to these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our analysis more precisely defines the role of probiotics for treating infantile colic. A more recent systematic review by Harb et al [17] focused on interventions in breast-fed infants only and concluded that probiotics, in particular L. reuteri , appear effective for reducing colic, although there are limitations to these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies provided sufficient evidence to conclude in meta-analyses that Lactobacillus reuteri DSM 17938 at a dose of 10 8 colony-forming units per day in breastfed infants decreased IC and was well tolerated and safe [2324], resulting in a reduction of parental discomfort and the number of consultations [13]. One study in mainly formula fed infants with the same L. reuteri strain yielded a negative result [25].…”
Section: Discussionmentioning
confidence: 99%
“…Concerns have been raised with regard to the impact of proton pump inhibitors on the gut microbiome and the association between using proton pump inhibitors and small bowel bacterial overgrowth in children 33, 34. There is sparse evidence for the efficacy of other medication, such as pain relieving agents, prokinetic drugs or over‐the‐counter remedies such as simethicone for treating infantile colic 28, 35, 36, 37, 38. However, parents of infants with colic are very likely to decide what medication they give their children without advice from their doctor 39, 40.…”
Section: Pharmacological Management Of Fgids In Early Lifementioning
confidence: 99%